2018
DOI: 10.3171/2018.2.focus17543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of telemedicine with in-person care for follow-up after elective neurosurgery: results of a cost-effectiveness analysis of 1200 patients using patient-perceived utility scores

Abstract: OBJECTIVEThe utility of telemedicine (TM) in neurosurgery is underexplored, with most of the studies relating to teletrauma or telestroke programs. In this study, the authors evaluate the cost-effectiveness of TM consultations for follow-up care of a large population of patients who underwent neurosurgical procedures.METHODSA decision-analytical model was used to assess the cost-effectiveness of TM for ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 26 publications
(24 reference statements)
1
53
0
Order By: Relevance
“…These visits have been replaced by telemedicine clinic visits, which have previously been validated in the neurosurgery population. [5][6][7][8][9] We have implemented Health Insurance Portability and Accountability Act (HIPPA)-compliant telehealth technology integrated into our electronic medical record (Epic, Epic Systems Corporation, Verona, Wisconsin). Neurosurgeons and their patients can communicate via secure video-conference feed using a computer, mobile device, or tablet.…”
Section: Clinic Schedulingmentioning
confidence: 99%
“…These visits have been replaced by telemedicine clinic visits, which have previously been validated in the neurosurgery population. [5][6][7][8][9] We have implemented Health Insurance Portability and Accountability Act (HIPPA)-compliant telehealth technology integrated into our electronic medical record (Epic, Epic Systems Corporation, Verona, Wisconsin). Neurosurgeons and their patients can communicate via secure video-conference feed using a computer, mobile device, or tablet.…”
Section: Clinic Schedulingmentioning
confidence: 99%
“…34 Notably, another study found that any potential reduction in efficacy may be offset by the cost-effectiveness and utilitarian benefits of telemedicine. 35 The cognitive demand imposed on users by different video conference platforms may be a key consideration in selecting the appropriate platform. Agnisarman et al 36 compared the usability of 4 platforms-Doxy.me, Vidyo, VSee, and Polycom-with a sample clinical scenario that included a log-in sequence, changing to full screen, muting the microphone, disabling video, communicating over chat, and concluding the session.…”
Section: Considerations In the Implementation Of Telehealthmentioning
confidence: 99%
“…Teleconsultation for daily routine, including its implementation for neurosurgical cases, is already practiced in many countries such as Norway, 3 United Kingdom, 7,8 USA, 9 Germany, 2,10 and India. 11 The advantages of this technology seem particularly convincing in rural areas. Nevertheless, the role of German neurosurgeons in teleconsultation is not yet clear.…”
Section: Experience With Teleconsultationmentioning
confidence: 99%